Knowledge and training needs on built environment and indoor health of Italian public health residents: a national survey - Capasso, L. (J Prev Med Hyg, 2017)
INTRODUCTION. The Working Group for Hygiene of Built Environment and the National Council of Residents of the Italian Society of Hygiene, Preventive Medicine and Public Health conducted a nation-wide survey to evaluate the knowledge and training needs on Built Environment and Indoor Health of Italian public health residents. RESULTS. The compliance was very high (52,4%), covering the totality of Italian postgraduate schools. The results underline a severe lack of theoretical formation and practical training, but also diffuse discrepancies across the country, and show a strong interest of residents on this topic. CONCLUSIONS. The authors propose to adopt a national core curriculum, and suggest some strategies to improve learning.